2017
DOI: 10.1177/2158244017730387
|View full text |Cite
|
Sign up to set email alerts
|

Practices That Support the Inclusion of Children With Autism Spectrum Disorder in Mainstream Early Childhood Education in Zimbabwe

Abstract: The international and national mandate to serve learners with special needs in regular education warrants examination of support practices for including learners with autism in Zimbabwe. Entrenched within the inclusive pedagogical philosophy, the current qualitative study executed individual interviews with 18 teachers, document analysis, and nonparticipant observations in the Midlands educational province of Zimbabwe to explore support practices for including learners with autism in regular Early Childhood De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…However, little other mention of ASD exists in this document. In a Zimbabwean context, participants in Majoko's (2017) research reported how the usage of reinforcements, structured routines, and academic and environmental modifications assisted in the inclusion of children with ASD in early childhood development classrooms. Still, Majoko (2017) noted the necessity of further teacher preparedness and training regarding inclusive practices in early learning settings for children with ASD in Zimbabwe.…”
Section: Child Care Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little other mention of ASD exists in this document. In a Zimbabwean context, participants in Majoko's (2017) research reported how the usage of reinforcements, structured routines, and academic and environmental modifications assisted in the inclusion of children with ASD in early childhood development classrooms. Still, Majoko (2017) noted the necessity of further teacher preparedness and training regarding inclusive practices in early learning settings for children with ASD in Zimbabwe.…”
Section: Child Care Reportsmentioning
confidence: 99%
“…In a Zimbabwean context, participants in Majoko's (2017) research reported how the usage of reinforcements, structured routines, and academic and environmental modifications assisted in the inclusion of children with ASD in early childhood development classrooms. Still, Majoko (2017) noted the necessity of further teacher preparedness and training regarding inclusive practices in early learning settings for children with ASD in Zimbabwe. In their literature review, Franz, Chambers, von Isenburg, and de Vries (2017) noted the lack of standardization and quality research methodologies in research studies on ASD in sub-Saharan Africa.…”
Section: Child Care Reportsmentioning
confidence: 99%
“…The explanations of ASD provided by participants above included descriptions of particular challenges faced, such as problems communicating, which aligns with similar descriptions in the literature of social interaction and communication challenges (Majoko 2017 ). Some complexities that characterise ASD were noted in teacher descriptions of ASD including sensory sensitivity and experiencing difficulty with understanding figurative language and sarcasm.…”
Section: Presentation and Discussion Of Findingsmentioning
confidence: 77%
“…Majoko ( 2017 ) argues that the description of characteristics associated with ASD is challenging, given the many individual differences amongst learners with ASD. We support this argument and acknowledge that not all learners with ASD can be described as experiencing identical challenges.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation